PENGARUH GREEN ACCOUNTING DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP PROFITABILITAS PERUSAHAAN ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2021-2023 - Sitompul, Julana Sari; Harahap, Junita Putri Rajana; Ovami, Debbi Chyntia; Fauzi, Indra (Worksheet : Jurnal Akuntansi, 2025)
This study aims to examine the effect of Green Accounting and Corporate Social Responsibility on the profitability of energy companies listed on the Indonesia Stock Exchange in 2021-2023. Determination of the sample using the purposive sampling method, the sample obtained in the period 2021-2023 was 39 observation data. The data used is secondary data. The data analysis technique used is multiple linear regression, by conducting a series of classical assumption tests to ensure the feasibility of the data. Data processing in this study uses panel data regression with the help of EViews software version 12. The results of this study indicate that Green Accounting has a positive and significant effect on profitability, Corporate Social Responsibility has a positive and significant effect on profitability. Based on the results of the simultaneous test, it shows that all independent variables have a simultaneous or joint effect on the dependent variable. The amount of contribution of independent variables to the company's profitability is 25.22%. While 74.78% of the company's profitability is influenced by other variables outside this study.